GENERAL OVERVIEW OF TUBERCULOSIS: CAUSES, SYMPTOMS, AND RISK FACTORS - Narmetova Yulduz Karimovna (Modern American Journals, 2025)
Tuberculosis (TB) remains a global health threat, exacerbated by factors such as drug resistance, co-infections, and social determinants of health. This comprehensive review examines various aspects of TB, including epidemiology, pathophysiology, diagnosis, treatment, prevention, and control measures. The bacterium Mycobacterium tuberculosis causes TB and primarily affects the lungs, although it can also affect other organs.